Christopher Marlowe's Doctor Faustus [Cliffs notes] - Fitzwater, Eva. (Lincoln : Cliffs, 1967)
A collection of seven critical essays on Marlowe's drama, arranged in chronological order of their original publication.
Includes bibliographical references
DELL
Keywords: Marlowe, Christopher, -- 1564-1593.; Faust, -- d. ca. 1540 -- In literature; Marlowe, Christopher, -- 1564-1593.; Faust, -- d. ca. 1540 -- In literature; Magicians in literature; Tragedy; English literature -- History and criticism